CHALLENGES IN MANAGING THE HEALTH WORKFORCE FOR UNIVERSAL HEALTH COVERAGE IN ANGOLA - Candido, Teresa Vilunga Chituko (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Human resource management in health is essential to achieving universal health coverage, particularly in countries facing significant structural challenges, such as Angola. Study aim: This study aims to describe the challenges in managing the health workforce for universal health coverage in Angola. Materials and methods: A narrative literature review was conducted using secondary sources, including scientific literature and official reports published in English and Portuguese between 2019 and 2023. Data were collected from documents issued by national and international health organizations, focusing on population statistics, health indicators, and information regarding the health workforce. Results: Angola has a population of over 36.7 million, which is projected to double by 2050. The health service coverage rate is approximately 45%, leaving about 20 million people without basic access. In terms of health indicators, 15% of the population faces catastrophic health expenditures, while 30% live in extreme poverty. In 2021, life expectancy at birth was 62.1 years. In 2023, tuberculosis incidence reached 339 cases per 100,000 inhabitants, while in 2022, malaria incidence was 235.9 cases per 1,000 inhabitants. Under-five mortality was 66.87 per 1,000 live births in 2022, and neonatal mortality was 26.03 per 1,000 live births in the same year. Maternal mortality stood at 221.9 per 100,000 live births in 2020. The main causes of death in 2021 were respiratory infections, malaria, and tuberculosis. By 2025, it is estimated that 1.6 million more people will have better health conditions, and 2.7 million more people will be covered by essential health services, as compared to 2018. In 2021, the national health network comprised 6,930 facilities (3,162 public and 3,768 private healthcare facilities) and more than 100,000 health professionals, including 7,716 physicians, 51,216 nurses, and 12,177 technologists. The density of healthcare workers per 10,000 inhabitants was 2.48 doctors, 16.45 nurses, and 3.91 technologists. Conclusions: Universal health coverage in Angola cannot be achieved without significant and sustained investment in the training, retention, and equitable distribution of health professionals. It is essential to ensure the presence of these professionals in both urban and rural areas, as well as in economically disadvantaged regions. Strengthening human resource management is crucial to addressing the country’s health and social challenges.